(untitled) (Comunicação & Inovação, 2017)
Postmodernity, by correcting the excesses of modernity, transformed the relation of individuals with themselves and with the audiovisual contents. In this context, social TV, considering the critical construction made in social networks, can be seen as a characteristic phenomenon of the period. For a better understanding of both concepts, this article proposes a content analysis of the tweets posted in 2015 during the exhibition of the fifth season of Game of Thrones.